Assessment of knowledge and practices of exclusive breastfeeding among rural women during the COVID-19 pandemic in Egypt: a cross sectional study - Noura El-Gamel; Amina El-Nemer (BMC Women's Health)
Abstract Background Worldwide exclusive breastfeeding is still recommended as a successful strategy even during the COVID -19 pandemic to lower infant morbidity and mortality. This study aimed to assess the knowledge and practices of exclusive breastfeeding among rural women during the COVID-19 pandemic. Methods A descriptive cross-sectional study was conducted at EL-Morabeen Family Medicine Center in rural Damietta, Egypt among 178 lactating women who were chosen by using the purposive sampling technique. A developed structured questionnaire consisting of four parts was used to gather data from March to May 2022. Univariate analysis for descriptive data and bivariate analysis through the chi-square test were performed. Results The current study revealed that 73% of the studied rural women did not receive any breastfeeding counseling during antenatal visits and 61.2% of them believed that coronavirus was transmitted through breastmilk. Only 15.2% of them breastfed their infant exclusively for 6 months, 88.2% of mothers delayed breastfeeding initiation after delivery and 48.3% administered the prelacteal feeds. A total of 98.3% of rural women had never made skin-to-skin contact, and 79.2% of them had not been vaccinated against COVID-19. Additionally, a statistically significant association between good knowledge and practice with highly educated women aged 26–30 years, with a monthly income of 4000–6000 L.E was found. Furthermore, only 26.4% and 26.1% of rural women had good knowledge and practice scores respectively. Conclusion Suboptimal breastfeeding practices, such as delayed onset of breastfeeding, low percentages of exclusivity, early weaning, prelacteal feeding administration, and lack of skin-to-skin contact during the COVID -19 pandemic were prevalent among the studied rural mothers. Breastfeeding counseling for all pregnant women and implementation of evidence-based practices in the health care system, such as the early initiation of breastfeeding and skin-to-skin contact, are recommended.